Stroke-specific swimming critical speed testing: Balancing feasibility and scientific rigour - Scott, B. E.; Burden, R.; Dekerle, J. (Journal of Human Kinetics, 2024)
This study aimed to assess the reliability of a two-distance critical speed protocol in the specialist strokes of national-level swimmers and understand the practical feasibility of extending the protocol to increase its validity. Thirty-two national-level swimmers (butterfly n = 7; backstroke n = 8; breaststroke n = 7; front crawl n = 10) swum three 200-m and three 400-m performance trials over a three-week period. Critical speed and supra-critical speed distance capacity were computed from the linear modelling of the distance-time relationship. Swimmers were subsequently asked whether they felt they could or would want to complete an 800-m trial as part of a three-distance critical speed protocol to enhance validity. Both 200-m and 400-m performances (coefficient of variation of < 2%) and derived critical speed (typical error of = 0.04 m·s-1; coefficient of variation of < 4%) were reliable for all strokes, while supra-critical speed distance capacity (typical error from 4 to 9 m; coefficient of variation from 13 to 45%) was not reliable. Response rates to the follow-up questions were 100%. Few butterfly swimmers said they felt they could complete an 800-m performance trial (39%), with more positive responses for breaststroke (71%), backstroke (100%), and front crawl swimmers (100%). Butterfly swimmers were significantly less likely to say they could or would want to complete an 800-m trial than backstroke and front crawl swimmers (p < 0.05). Including a third distance 800-m trial to increase critical speed validity would not be acceptable to butterfly swimmers, would be challenging to breaststroke swimmers, but would be acceptable to front crawl and backstroke swimmers.